Apuntes sobre Ricardo Palma y el español del Perú - Martos Carrera, Marco (2018)
Due to linguistic colonization and language hybridization due to its permanentcontact with indigenous languages, Spanish is a language that has been changingover time, acquiring variations in each region of America. In the case of Peru,the imposition of a language in a territory that had many others has generatedthe emergence of Peruvian idioms, incorporating many words of native origin intothe general language. The figure of Ricardo Palma, is important, not only for hisliterary writing, but for his attitude of closed defense of the Andean Castilian andthe incorporation of our words to the dictionary of the Royal Spanish Academy in1892.